2020
DOI: 10.9734/ijtdh/2020/v41i830311
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Smear Morphology- A Red Flag in COVID-19

Abstract: Covid-19 pandemic has affected the whole word medically, economically and emotionally. It is being considered as the biggest pandemic after the Spanish flu, with very high degree of morbidity and mortality in those with complications. The diagnostic and treatment criteria of this novel virus are being updated frequently as nothing much is known about it. This highlights the importance of hematology lab parameters in Covid diagnosis and prediction of disease progression. Multiple studies on complete blood count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 2 publications
2
12
0
Order By: Relevance
“…In the present study, the findings observed in CBC were lymphopenia (22%), monocytopenia (20%) and thrombocytopenia (48%) with neutrophilia (16%). These corroborated with findings reported by Singh S et al, Luke F, et al and Singh A 5,20,21 . Data by Luke F et al 5 were also in concert with present findings albeit with higher percentages of reported lympho‐/mono‐cytopenia, thrombocytopenia and leucocytosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the findings observed in CBC were lymphopenia (22%), monocytopenia (20%) and thrombocytopenia (48%) with neutrophilia (16%). These corroborated with findings reported by Singh S et al, Luke F, et al and Singh A 5,20,21 . Data by Luke F et al 5 were also in concert with present findings albeit with higher percentages of reported lympho‐/mono‐cytopenia, thrombocytopenia and leucocytosis.…”
Section: Discussionsupporting
confidence: 93%
“…These corroborated with findings reported by Singh S et al, Luke F, et al and Singh A. 5 , 20 , 21 Data by Luke F et al 5 were also in concert with present findings albeit with higher percentages of reported lympho‐/mono‐cytopenia, thrombocytopenia and leucocytosis. In a solitary case report by Singh A et al on morphology of COVID‐19‐affected cells in PBS, similar findings of neutrophilia with relative lymphocytopenia and monocytopenia have been documented.…”
Section: Discussionsupporting
confidence: 93%
“…18 Also noted were large granular lymphocytes, reactive monocytoid and plasmacytoid forms and blastoid forms, activated monocytes with large bizarre forms, vacuoles and granules. 18,19 In a study by Zhang et al by analysing monocyte subset it was shown that the peripheral smear in COVID-19 is different from any other viral illness. 20 More recent updates suggest that cytokine storm and hyperinflammation which is seen in COVID-19 infection can lead to such quantitative and qualitative abnormalities in hematological parameters, possibly in the form of secondary hemophagocytic lymphohistiocytosis, leading to possibility of relapse or fatal multi-organ failure.…”
Section: Resultsmentioning
confidence: 99%
“…Alteration in morphology of cells of the peripheral blood in COVID-19 as is evident by few studies [9][10][11][12][13]. In a study of 28 patients with confirmed COVID-19 infection with varying degrees of severity, morphological and functional changes of monocytes/ macrophages were noted using wright stained smears and flow cytometry, that was predictive of the severity of disease, likelihood of ICU admission, length of hospital stay and full recovery [9] Singh et al in his case report of COVID 19 patient, found following changes in peripheral blood smear.…”
Section: Discussionmentioning
confidence: 97%